2017
DOI: 10.18632/oncotarget.18387
|View full text |Cite
|
Sign up to set email alerts
|

CXCL13 is androgen-responsive and involved in androgen induced prostate cancer cell migration and invasion

Abstract: Androgen receptor (AR) is a key transcription factor playing a critical role in prostate cancer (PCa) initiation and progression. However, the molecular mechanisms of AR action in prostate cancer are not very clear. CXCL13, known as B cell attracting chemokine1 (BCA-1), is a member of CXC chemokine family and relevant to cancer metastasis. This study shows that CXCL13 is an androgen-responsive gene and involved in AR-induced PCa cell migration and invasion. In clinical specimens, expression of CXCL13 in PCa ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
0
24
1
Order By: Relevance
“…1B). Among them, SPP1 [19], GCNT3 [11], TMPRSS4 [20], SPINK1 [21], HABP2 [22], and CXCL13 [23] are known oncogenes for tumor i-genesis, while two, namely TMPRSS4 and HABP2, were identified as oncogenes in lung cancer. The top 10 up-regulated mRNAs in NSCLC tissues are listed in Table 2.…”
Section: Differentially Expressed Mrnas In Nsclc Tissuesmentioning
confidence: 99%
“…1B). Among them, SPP1 [19], GCNT3 [11], TMPRSS4 [20], SPINK1 [21], HABP2 [22], and CXCL13 [23] are known oncogenes for tumor i-genesis, while two, namely TMPRSS4 and HABP2, were identified as oncogenes in lung cancer. The top 10 up-regulated mRNAs in NSCLC tissues are listed in Table 2.…”
Section: Differentially Expressed Mrnas In Nsclc Tissuesmentioning
confidence: 99%
“…Overexpression of CXCL9 and 10 is found in GC tissue compared to normal gastric tissue (Raja et al, 2017), however, data on CXCL11 expression in GC was not found. CXCL13 (C-X-C motif chemokine ligand 13) is related to cell proliferation and associated with poor prognosis in several neoplasms, including GC (Fan et al, 2017;Wei et al, 2018). Obayashi et al (2016) showed CXCL13 overexpression primarily around lymphoid follicles in gastric biopsies from infected children; while Ikuse et al (2012) showed overexpression of CXCL9, 10, 11, 13, and CCL18 in gastric tissue of infected children, all of whom had histological inflammation and nodular gastritis.…”
Section: Extracellular Secreted Proteinsmentioning
confidence: 99%
“…According to this score, CDI patients were divided into groups of mild to moderate disease and severe disease using a severity score index according to the guidelines of the "Society for Healthcare Epidemiology of America and the Infectious Diseases Society of America" (SHEA-IDSA) as follows: mild to moderate disease¼leukocytosis ≤ 15,000 cells/ml and creatinine ≤ 1.5 times the premorbid level; severe disease ¼ leukocytosis ≥ 15,000 cells/ml or serum creatinine ≥ 1.5 times the premorbid level. Severe disease was de ned also as a serum albumin level of ≤ 3 g/dl at the time of active infection [22,23].…”
Section: Disease Severity Scoring and Demographic Data Collectionmentioning
confidence: 99%